High-throughput phenotypic screening of the human spermatozoon. Issue 1 (27th December 2021) - Johnston, Zoe C; Gruber, Franz S; Brown, Sean G; Norcross, Neil R; Swedlow, Jason; Gilbert, Ian H; Barratt, Christopher L R
Abstract : Despite recent advances in male reproductive health research, there remain many elements of male infertility where our understanding is incomplete. Consequently, diagnostic tools and treatments for men with sperm dysfunction, other than medically assisted reproduction, are limited. On the other hand, the gaps in our knowledge of the mechanisms which underpin sperm function have hampered the development of male non-hormonal contraceptives. The study of mature spermatozoa is inherently difficult. They are a unique and highly specialised cell type which does not actively transcribe or translate proteins and cannot be cultured for long periods of time or matured in vitro . One large-scale approach to both increasing the understanding of sperm function and the discovery and development of compounds that can modulate sperm function is to directly observe responses to compounds with phenotypic screening techniques. These target agnostic approaches can be developed into high-throughput screening platforms with the potential to drastically increase advances in the field. Here, we discuss the rationale and development of high-throughput phenotypic screening platforms for mature human spermatozoa and the multiple potential applications these present, as well as the current limitations and leaps in our understanding and the capabilities needed to overcome them. Further development and use of these technologies could lead to the identification of compounds which positively or negatively affect sperm cell motility or function or novel platforms for toxicology or environmental chemical testing among other applications. Ultimately, each of these potential applications is also likely to increase the understanding within the field of sperm biology.